آثار الذكاء الاصطناعي على الامن السيبراني دراسة حالة الجزائري - عبد الباسط ،عيساوي; سفيان ،زيتون (جامعة الوادي University of El Oued, 2024)
تحاول هذه الدراسة البحث في موضوع استخدامات الذكاء الاصطناعي وعلاقته بالأمن السيبراني، حيث تطرقنا في الفصل الأول الذي يعالج فيه مفاهيم الدراسة بدأ بالذكاء الاصطناعي وأهميته في حل المشكلات، ثم عرّجنا إلى الأمن السيبراني وأبعاده وأهميته وأما في الفصل الثاني ذكرنا فيه استخدامات الذكاء الاصطناعي في الأمن السيبراني والتحديات الأمنية، ويحتوي الفصل الثالث على دراسة تحليلية لاستخدامات الإنترنت في الجزائر باعتماد إستراتيجيات من قبل الدولة لتحقيق الأمن السيبراني حيث كرّست الدولة الجزائرية تحديات أمنية غاية في الأهمية والنجاح. This study attempts to research the topic of the uses of artificial intelligence and its relationship to cyber security, as we discussed in the first chapter, which deals with the concepts of the study. We started with artificial intelligence and its importance in solving problems, then we went to cyber security, its dimensions and importance, and in the second chapter we mentioned the uses Artificial intelligence in cyber security and security challenges. The third chapter contains an analytical study of the uses of the Internet in Algeria, adopting strategies by the state to achieve cyber security, as the Algerian state has devoted itself to extremely important and successful security challenges.
ماستر سياسة عامة